2016
DOI: 10.1589/jpts.28.1427
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sole vibration stimulation on Korean male professional volleyball players’ jumping and balance ability

Abstract: [Purpose] The purpose of this study was to investigate differences in jumping ability and lower limb balance ability elicited by plyometric training and vibration exercise, of volleyball players with and without ankle injuries, which frequently occur among Korean professional volleyball players. [Subjects and Methods] Twenty-eight volleyball players were divided into the following groups: plyometric with ankle injury (PAI) group; plyometric with non-ankle injury (PAN) group; vibrator with ankle injury (VAI) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The tendency of jumping results improvement among volleyball players was revealed after the block of vibrating loads fulfillment [8]. 14 professional volleyball players took part in the experiment, which lasted 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…The tendency of jumping results improvement among volleyball players was revealed after the block of vibrating loads fulfillment [8]. 14 professional volleyball players took part in the experiment, which lasted 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the participants did not change between test sessions. They had to meet the following criteria to participate in this study: (1) history of professional volleyball training for at least 5 years, (2) no participation in any formal agility training programs within the 6 months preceding this study, and (3) commitment to participate in agility training program for a minimum of three times per week during the 6-week training period. All participants gave informed consent, and the Committee for the Protection of the Rights of Human Subjects granted approval for this project.…”
Section: Subjectsmentioning
confidence: 99%
“…In a moving defensive position, in addition to executing rapid lateral movements and alternating footsteps, defenders must precisely control the direction and speed of the ball's bounce after it has been received to achieve an effective defense. The results of several studies have indicated that plyometric training can enhance vertical jump performance, 1,2 acceleration, muscular power, and agility. 1,[3][4][5] Plyometric training is a form of strength training that is often used with athletes, particularly those in sports who require jumping ability and agility, to enhance their strength and explosiveness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations